A comparison of the Nzi, Horse Pal® and Bite‐Lite® H‐traps and selected baits for the collection of adult Tabanidae in Florida and North Carolina. Issue 1 (14th May 2018) - Kline, Daniel L.; Hogsette, Jerome A.; Rutz, Donald A.
ABSTRACT: Despite the veterinary and medical importance of horse flies, deer flies, and yellow flies, only a few trap types have been evaluated to monitor adult population dynamics. Currently, three trap types are being utilized (H‐trap, Horse Pal® (HP), and Nzi trap), but no head‐to‐head comparisons have been reported. Thus, we conducted comparative trapping studies in Florida and North Carolina. At two study sites in Florida, the efficacy of all three trap types was compared, but only the H‐trap and HP were compared in North Carolina. Although trap type was significant at all sites, the trap type which caught the most specimens was not the same. In Florida at the Lower Suwannee Wildlife Refuge (LSWR) site, the H‐trap caught the most specimens (2, 006), followed in decreasing order by Nzi (938) and HP (541). At the Cedar Ridge Ranch site, the Nzi caught significantly more specimens (1, 439) than the H‐trap (215) and HP (161), which were not significantly different from each other. In North Carolina, the H‐trap caught approximately twice as many specimens as the HP (1, 458 vs 720). These trap comparison studies were followed up by a study on the efficacy of various bait combinations: (No Bait (NB), dry ice only (DI), Trap Tech Lure (TTL) only, and DI + TTL), which was conducted only at the two Florida sites with H‐traps. At both sites, bait combinations significantly affected trap collections. One pattern (DI +TTL > DI > TTL > NB) was recorded at the LSWR, while at the Cedar River Ranch the pattern was DI > DI +TTL > TTL > NB. Our data showed that trap type and bait combination significantly influence overall adult tabanid abundance as well as individual species composition.